2017
DOI: 10.1111/tid.12738
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of cystic fibrosis patients colonized by Scedosporium species following lung transplantation: A single‐center 15‐year experience

Abstract: It appears to us that scedosporial colonization may not be a contraindication for LT in CF patients, as long as S. apiospermum complex is involved and a life-long azole prophylaxis prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Infection with certain microorganisms (e.g. Burkholderia cepacia complex, nontuberculous mycobacterium, molds such as scedosporium, multi-drug resistant or increasingly resistant microorganisms) is associated with worse outcomes following lung transplantation [18,61,[84][85][86][87][88][89]. These microorganisms may be considered absolute contraindications at some transplant programs and acceptable at others While there are established international consensus recommendations for the selection of lung transplant candidates, published by the ISHLT [61], each lung transplant program has developed its own specific criteria for transplant candidacy and listing.…”
Section: The Cf Foundation Recommends Cf Clinician Consultation Withmentioning
confidence: 99%
“…Infection with certain microorganisms (e.g. Burkholderia cepacia complex, nontuberculous mycobacterium, molds such as scedosporium, multi-drug resistant or increasingly resistant microorganisms) is associated with worse outcomes following lung transplantation [18,61,[84][85][86][87][88][89]. These microorganisms may be considered absolute contraindications at some transplant programs and acceptable at others While there are established international consensus recommendations for the selection of lung transplant candidates, published by the ISHLT [61], each lung transplant program has developed its own specific criteria for transplant candidacy and listing.…”
Section: The Cf Foundation Recommends Cf Clinician Consultation Withmentioning
confidence: 99%
“…In addition, the presence of Aspergillus spp. in the same sample could also hamper the growth of S/L . In a monocentric Australian study including 59 colonized patients, S/L were found in association with Aspergillus sp in 29% of cases .…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent study in the era of mold-active triazole prophylaxis suggests outcomes may be favorable for patients with S. apiospermum species complex colonization. 27 Among eight CF patients colonized with S. apiospermum species complex prior to transplant, none developed invasive Scedosporium infection posttransplant and seven survived more than 1-year posttransplant (provisional median survival 1.9 years, range 0.2-12.5). Four patients became free of S. apiospermum species complex colonization immediately posttransplant and another three patients within 1 year.…”
Section: Clinical Manifestationsmentioning
confidence: 94%